Psychometric Validation of the Mathematics Attitude Questionnaire (MAQ): A Confirmatory Factor Analysis Approach - Danlami, Kazaik Benjamin (International Journal of Mathematics and Mathematics Education (IJMME), 2025)
Purpose – Mathematics underperformance remains a global challenge, especially in low-resource and conflict-affected contexts where students often face affective barriers such as anxiety, low enjoyment, and self-doubt. Although the Mathematics Attitude Questionnaire (MAQ) has been widely used internationally, its structural validity has rarely been examined in sub-Saharan Africa. This study aimed to validate the MAQ among Nigerian senior secondary school students. Methodology – A cross-sectional quantitative design under a post-positivist paradigm was employed. Using multistage sampling, 204 students (mean age = 16.8 years; 55% male) from three educational zones in Kaduna State completed a culturally adapted 31-item MAQ. Exploratory Factor Analysis (EFA) was first conducted to identify the underlying structure, followed by Confirmatory Factor Analysis (CFA) in Mplus to evaluate model fit. Reliability was assessed using coefficient omega, while validity was examined through Average Variance Extracted (AVE) and Heterotrait-Monotrait ratio (HTMT). Findings – EFA supported a two-factor structure: Enjoyment of Mathematics and Perception of Incompetence. CFA indicated suboptimal model fit (CFI = .831; TLI = .808; RMSEA = .141; SRMR = .100), though factor loadings (.49–.80) were significant. Reliability was strong (ω = .933; .872), AVE exceeded .58, and HTMT (.67) supported discriminant validity. The results affirm the relevance of the two constructs but highlight the need for theoretical refinement and cultural adaptation. Novelty – This is the first empirical validation of the MAQ using CFA in Nigeria, addressing a critical methodological gap in sub-Saharan mathematics education research. Significance – The validated MAQ provides educators, curriculum developers, and policymakers with a reliable diagnostic tool to assess and strengthen students’ affective engagement, guiding interventions to enhance enjoyment, self-efficacy, and mathematics performance.